The Influence Of Social Media Usage And Brand Awareness On Purchasing Decisions For Skincare Brand Skintific For Students In Palembang City - Maryani, Tarwiyah; Naruliza, Esty; Mario, Asma (Universitas Dehasen Bengkulu, 2024)
The increasing trend of using social media as a means of promotion and product information, as well as the importance of brand awareness in influencing purchase decisions, there are skintific skincare products under the Skintific brand for students in the city of Palembang. This study was made to determine the influence of social media use and brand awareness on the purchase decision of Skintific brand skincare in students in the city of Palembang both simultaneously and partially. This study uses a quantitative descriptive approach with the accidental sampling method, where data is collected through the distribution of questionnaires to 272 student respondents who have known or used Skintific products. With an error level of 10% or 0.1. The test is carried out in three stages, namely validity and reliability test, classical assumption test, and hypothesis test. The analysis technique used is multiple linear regression to test the influence of each independent variable on the dependent variable. In hypothesis testing, both simultaneously and partially have a significant effect on the purchase decision. The results showed that the value of the determination coefficient (R2) of 0.601 or 60.1% of the variation in the dependent variable can be explained by the independent variable. The remaining 39.9% were explained by other factors not included in this study. These findings suggest that marketing strategies through social media and increased brand awareness are essential to drive consumer purchasing decisions, particularly among college students.